Twenty-Two-Year Study of the Spread and Impact of Hemlock Woody Adelgid and Elongate Hemlock Scale in Southwest Virginia - Thomas J. McAvoy; Ryan Mays; Mohamed Salem; Lori Chamberlin; Rusty Rhea; Christopher Asaro; Scott M. Salom (Journal of Forestry, 2025)
This 22-year study examined the impact and dispersal of the hemlock woolly adelgid (HWA) and the elongate hemlock scale at 67 sites in southwest Virginia. A hemlock stand health index was based on percent foliage density, live crown ratio, live branches, live tips, new foliage, and live trees at each site. At the beginning of the study, hemlock health at all sites was good. After 22 years hemlock health had declined to a poor condition and mortality averaged 30%. Differences in health decline were found among the three physiographic mountain regions. Analysis of the variables measured indicated that hemlock stand health decline was positively correlated with the percentage of branches infested with HWA, hemlock diameter at breast height (dbh), and total tree basal area per hectare and negatively correlated with latitude. Crown density, the inverse of Forest Inventory and Analysis (FIA) canopy foliage transparency could be used as a standalone hemlock health measurement.

Increases in summer temperatures decrease the survival of an invasive forest insect - Angela M. Mech; Patrick C. Tobin; Robert O. Teskey; J. Rusty Rhea; Kamal J. K. Gandhi (Biological Invasions, 2018)